La costituente libertaria di Camillo Berneri Un disegno politico tra federalismo e anarchismo - Sacchetti, Andrea (Premio Tesi di Dottorato, 2019)
This work aims at identifying the historical, cultural, political and strategic reasons that in 1935 led the anarchist Camillo Berneri to write the Constitution of the Italian Federation of Socialist Municipalities (based on the Italian acronym, FICS), an original constitution project with no predecessors within the anarchist movement which, unsurprisingly, remained unpublished for a long time. The research aims at explaining its existence within the Berneri's intellectual path, interpreting it as the result of a long elaboration of his ideas and operational proposals on libertarian federalism. This maturation is characterized by the presence of different influences, with those shared with Gaetano Salvemini's concrete and problematic approach being the decisive ones.